2018
DOI: 10.1186/s40168-018-0465-9
|View full text |Cite
|
Sign up to set email alerts
|

Setting the pace: host rhythmic behaviour and gene expression patterns in the facultatively symbiotic cnidarian Aiptasia are determined largely by Symbiodinium

Abstract: BackgroundAll organisms employ biological clocks to anticipate physical changes in the environment; however, the integration of biological clocks in symbiotic systems has received limited attention. In corals, the interpretation of rhythmic behaviours is complicated by the daily oscillations in tissue oxygen tension resulting from the photosynthetic and respiratory activities of the associated algal endosymbiont Symbiodinium. In order to better understand the integration of biological clocks in cnidarian hosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 39 publications
4
62
1
Order By: Relevance
“…The comparative ΔΔ CT s method was used, and fold changes were calculated using the 2 −ΔΔ Ct formula to estimate the relative difference in the number of transcripts between the aposymbiotic and symbiotic samples. Four potential house‐keeping genes were tested: 28S ribosomal RNA gene (Rodriguez‐Lanetty, Phillips, & Weis, ), beta‐actin (Rodriguez‐Lanetty et al, ), 40S ribosomal protein S7 (Lehnert et al, ), and encoding ribosomal protein L11 (RPL11; Sorek et al, ). Samples were normalized to the latter, which was the best performing one and showed the most stable expression pattern across all samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative ΔΔ CT s method was used, and fold changes were calculated using the 2 −ΔΔ Ct formula to estimate the relative difference in the number of transcripts between the aposymbiotic and symbiotic samples. Four potential house‐keeping genes were tested: 28S ribosomal RNA gene (Rodriguez‐Lanetty, Phillips, & Weis, ), beta‐actin (Rodriguez‐Lanetty et al, ), 40S ribosomal protein S7 (Lehnert et al, ), and encoding ribosomal protein L11 (RPL11; Sorek et al, ). Samples were normalized to the latter, which was the best performing one and showed the most stable expression pattern across all samples.…”
Section: Methodsmentioning
confidence: 99%
“…ΔΔCTs method was used, and fold changes were calculated using the 2 −ΔΔCt formula to estimate the relative difference in the number of transcripts between the aposymbiotic and symbiotic samples. Sorek et al, 2018). Samples were normalized to the latter, which was the best performing one and showed the most stable expression pattern across all samples.…”
Section: Real-time Pcr For Anemone Candidate Transporters Of Interestmentioning
confidence: 99%
“…We originally hypothesized that the mammalian 12h clock evolved from the circatidal clock of coastal and estuarine animals that modulate their behavior in tune to the ~12.4 hour ebb and flow of the tides Zhu et al, 2017), which were also established independently from the circadian clock (III et al, 2008;Naylor, 1996;Takekata et al, 2012;Takekata et al, 2014;Zhang et al, 2013). To seek further support for our hypothesis, we analyzed two recently published time series RNA-Seq dataset of two marine animals harboring circatidal clock, aposymbiotic sea anemone Aiptasia diaphaha (Sorek et al, 2018) and the limpet Cellana rota . In both cases, we found large overlap of 12h-cycling transcritptome between mouse and these two species ( Figures 7A-C, S7A-C, Table S12).…”
Section: The 12h Rhythms Of Cedif and Nucleotide Metabolism Gene Exprmentioning
confidence: 88%
“…Consensus XBP1s binding motifs located at each gene promoter are also shown. (Q) RNA-Seq data for representative genes in (Sorek et al, 2018) and mouse liver, with both raw data and superimposed ~12h rhythms shown for the mouse liver data. (B) Predicted interactive network construction of these conserved 12h-cycling genes using STRING (Szklarczyk et al, 2015).…”
Section: Post-hoc Analysis Of Serum Synchronized Mmh-d3 Transcriptomementioning
confidence: 99%
See 1 more Smart Citation